Autozoner: an algorithm for automatic thermal zoning of buildings with unknown interior space definitions. Issue 2 (3rd March 2016) - Dogan, Timur; Reinhart, Christoph; Michalatos, Panagiotis
Abstract : In this paper, we present a general algorithm to automatically convert arbitrary building massing models into multi-zone building energy models (BEM). The algorithm follows current guidelines for thermal zone discretization of BEMs when actual interior space boundaries are yet undefined. Envisioned applications are for rapid model generation during schematic building design as well as for urban massing studies. We present an argument that current recommendations for separating core from perimeter zones effectively follow a straight-skeleton subdivision. Following a step-by-step explanation of the procedure, a number of example building shapes of varying complexity are shown to demonstrate the algorithm's robustness and suitability for automated multi-zone BEM generation. Going forward, it is recommended that the algorithm is adopted by software developers to ensure more consistent thermal model production within the building simulation community.